Thermal analysis for the integrated spent fuel pool of the Chinshan plant in the decommissioning process. (September 2018) - Chen, Yen-Shu
Highlights: The Chinshan plant will start decommissioning in 2018. The spent fuel pool of the Chinshan plant is almost full. The reactor cavity will be remained connected with the spent fuel pool. Analysis models are developed using GOTHIC. The available period of the cooling systems are evaluated. Abstract: The Chinshan plant in Taiwan will start decommissioning in December 2018. However, the remaining storage capacity of the spent fuel pool (SFP) is insufficient to load one full-core fuel into it. In addition, the dry cask storage facility has not been approved and cannot be used to load the old fuel that has been in the SFP for years. Thus, the reactor core will be used to contain fuel and the reactor cavity is planned to remain connected with the SFP at the beginning of decommissioning. The alternative decay heat removal strategy will be applied to the integrated SFP cooling. Thermal analyses for the integrated SFP are performed with GOTHIC in this study. The period that the Residual Heat Removal (RHR) system should be operable is evaluated. A lumped model is developed to calculate the pool temperature during normal condition, and the results are in good agreement with those from the simplified energy balance equations. A detailed model is also developed for the loss-of-coolant accident of the integrated SFP. Based on the results of the most limiting case which is the recirculation line break accident, the RHR system should be remained operable for 1800 days after the decommissioning starts. Currently, both of the Chinshan units are not in operation. The real shutdown period is sufficiently longer than that assumed in this study. Safety of the integrated SFP in the decommissioning process is further ensured.